Use of wearable technologies for analysis of activity recognition for sports - Sharma, Anil; Al-Dala’in, Thair; Alsadoon, Ghossoon; Alwan, Ali Amer (IEEE, 2021)
Activity recognition and enhance performance are the major issues that are faced by wearable technology devices. Therefore, in this paper, we present an exploratory study to examine and evaluate the current issues with wearable technology for analysis of activity recognition for sports. These issues can be controlled by implementing a high sensor and WSN technologies using components such as– Stimuli signal, Data recognition and analysis, and Physical testing. The study utilised the verified taxonomy based on wearable technology, which aims to use effective technology. Raw and processed data has been gathered from different sources. The study shows that there is a major gap in the previous research studies and most of the studies only investigated some of the component of the Wearable Technologies for Analysis of Activity recognition for sports which make it inefficiency for current researchers.